Pre-IPO financial performance and offer price estimation: Evidence from India - Ajay Yadav; Jaya Mamta Prosad; Sumanjeet Singh (Journal of Risk and Financial Management, 2023)
The primary focus of this paper is to develop an empirical model to study the relationship between key Financial Performance Indicators and IPO Offer Prices. It seeks to assist Indian IPO investors to make more informed decisions by advancing their knowledge about relevant Pre-IPO Financial Performance Indicators that are effective predictors of Offer Price. The purpose is this study is to provide all the stakeholders with an approach to evaluate the Offer Price of IPOs. This will help the stakeholders to overcome pricing anomalies. The companies listed in the National Stock Exchange of India between the financial years 2015-2016 to 2020-2021 are taken as the sample of the study. The secondary data are analyzed by constructing a multiple linear regression model. This study uses a range of fundamental factors related to financial performance in a single framework to demonstrate that an IPO Offer Price can be assessed by its Pre-IPO Financial Performance. The findings of this study validate the objectives of the model constructed. This research shows that the Pre-IPO Financial Performance has an influential role in explaining the IPO offering price. The results of the study show that variables such as Net Asset Value (NAV), Return on Assets (ROA), Profit after Tax (PAT), and Return on Net Worth (RONW) have a substantial impact on IPO Offering Price. The findings of the research will assist IPO issuers in pricing their offerings better and more competitively. Furthermore, this study will also minimize the gap between offering and listing prices to prevent speculative failure. The study will help investors with minimal resources to evaluate the value of any IPO issue. An IPO's value can be fairly estimated, and investors can decide whether the issue is worth investing in or not.
Keywords: G10; G11; G14; 650; Financial Performance Indicators; IPO; offer price